PENGEMBANGAN KURIKULUM: Kajian atas Pemahaman dan Kesiapan Guru Madrasah dalam Melaksanakan Kurikulum 2013 - Nelli Murodah (Wahana Islamika: Jurnal Studi Keislaman, 2019)
This research is qualitative research that analyzes the understanding and readiness of the teachers of MIS Pandanarum Tirto Pekalongan in the implementation of the 2013 curriculum. Data was collected by in-depth interviews, participatory observations, and documentation studies. Data analysis used an interactive analysis model which was presented by Miles and Hubermen. The results showed that the teachers of MIS Pandanarum Tirto Pekalongan did not have a sufficient understanding of the 2013 curriculum. This was seen in the teachers's lack of understanding of the 2013 curriculum definition, the principles of developing the 2013 curriculum, and the aspects that became the basis of the 2013 curriculum. However, they knew that there was a difference between the 2013 curriculum and the previous curriculum. The difference was in the time allocation that increased, and the thematic learning approach that they used. Meanwhile, the readiness for the implementation of the 2013 curriculum showed that there was no mature readiness from teachers in dealing with and implementing the 2013 curriculum that was refined and re-applied by the Government in the 2017/2018 school year. Thus, it was evident that the problem of teachers’s readiness was one of the crucial things in implementing the 2013 curriculum.